Peptides in plant reproduction—small yet powerful - Yan, Chun-Lin; Guan, Kai-Xun; Lin, Hong; Feng, Ting; Meng, Jiang-Guo (Frontiers in Plant Science, 2025)
Peptides, currently being considered as a novel class of plant hormones, play diverse roles in plant growth and development. Peptides trigger signaling by binding to receptors and co-receptors, thus activating cellular signaling pathways. Recently, peptides have been extensively investigated in plant reproduction-related processes, ranging from gametes development to gametes fusion. In this review, we summarize recent advancements related to the role of peptides in plant reproduction and discuss challenges that need to be addressed urgently.